Navigating Pedagogical Approaches: The Role of Rewards and Punishments in Fostering Student Discipline and Religious Commitment in Islamic Education - Citra Solehati; Haris Riadi; Rusiah (International Journal of Community Engagement Payungi, 2025)
This study examines the role of reward and punishment in improving student discipline and religious commitment in Islamic Religious Education (PAI) at SMAN 1 Bantan, Bengkalis. The research investigates how the implementation of these strategies affects students' academic and moral development in the context of Islamic education. The study aims to analyze the types of rewards and punishments applied, their effectiveness in improving discipline, and their contribution to forming religious commitment. A qualitative case study approach was employed, with purposive sampling involving PAI teachers, the vice principal, and 10–15 students. Data were collected through semi-structured interviews, observations, and document analysis. Interviews explored participants’ experiences, observations focused on classroom behavior, and documents were reviewed to understand policy implementation. Data were analyzed using Miles, Huberman, and Saldana’s interactive model: data condensation, display, and conclusion drawing. The findings show that material and symbolic rewards enhance motivation and positive behavior, while constructive punishments reinforce discipline. The integration of spiritual and moral values makes Islamic education distinct from conventional behaviorist approaches. Overall, the effective use of rewards and punishments strengthens student discipline and religious commitment, contributing to holistic character development. The study recommends further longitudinal and comparative research to examine long-term impacts on students’ academic and spiritual growth.